La Pampa Agroclimatic risk areas for four crop rotation schedules in the agricultural eastern region of La Pampa (Argentina) (Semiárida, 2018)
Climatic risks imply the probability of occurrence of extreme weather conditions, events that can threaten nature and human activities with a particular pattern of low frequency. They are termed agroclimatic risks when affecting farm production. The aim of this work was to assess an index of agroclimatic risk (ACR), based on the study of soil water climatology and simulation of different crop rotation schedules. The ACR index scoring was based on a scale of values running from 0 (minimum risk) to 1 (maximum risk). Four crop rotation schedules, under conditions of dry-land farming, were tested in 21 sites all over the Eastern region of La Pampa province: fallow land - wheat crop (FL-WC), lucerne pasture - wheat crop (LP-WC), fallow land - sunflower crop (FL-SC) and winter annual grass pasture - sunflower crop (WP-SC). Maps, generated with information involving the application for decades of FL-WC, LP-WC, FL-SC and WP-SC rotation schedules, showed the yearly occurrence of partial or absolute droughts during the warm semester. Rotation Schedule FL-WC exhibited lower ACR values (0.1 to 0.4) than LP-WC (0.1 to 0.6), FL-SC (0.4 to 0.5) and WP-SC (0.4 to 0.5 ). In all cases, ACR index took higher values for the Centraland South-Eastern regions than the North-Eastern region of La Pampa province.
Keywords: climate risk index (RAC); crop; rotations; La Pampa